A étant un angle aigu, montrer que :
- (cos a + sin a)² = 1+2 cos a × sin a
- (cos a - sin a)² = 1-2 cos a × sin a
- (cos a - sin a)² + (cos a + sin a)² = 2
- cos² a - sin² a = 1- 2 sin² a = 2cos² a -1
- cos⁴a + sin⁴a = 1-2 cos² a × sin² a
( RAPPEL : (x²)² = x⁴)

1

Réponses

2014-04-18T10:54:13+02:00
(cosa+sina)²=cos²a+2sinacosa+sin²a
sin²a+cos²a=1
(cosa+sina)²=1+2sinacosa

(cosa-sina)²=cos²a-2sinacosa+sin²a
sin²a+cos²a=1
(cosa+sina)²=1-2sinacosa

(cosa+sina)²+(cosa-sina)²=1+2sinacosa+1-2sinacosa=2

cos²a-sin²a=cos²a+sin²a-sin²a-sin²a=1-2sin²a
cos²a-sin²a=cos²a+cos²a-cos²a-sin²a=2cos²a-(cos²a+sin²a)=2cos²a-1

cos⁴a + sin⁴a=(cos²a+sin²a)-2sin²acos²a=1-2sin²acos²a